2017
DOI: 10.1016/j.pscychresns.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous subcortical morphology in boys, but not girls, with ADHD compared to typically developing controls and correlates with emotion dysregulation

Abstract: There has been limited investigation of volume and shape difference in subcortical structures in children with ADHD and a paucity of examination of the influence of sex on these findings. The objective of this study was to examine morphology (volume and shape) of subcortical structures and their association with emotion dysregulation (ED) in girls and boys with ADHD as compared to their typically-developing (TD) counterparts. Participants included 218 children ages 8-12 years old with and without DSM-IV ADHD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 65 publications
(75 reference statements)
6
42
2
Order By: Relevance
“…Based on previous findings of ADHD-related sex differences in basal ganglia volumes (Qiu et al, 2009; Seymour et al, 2017), we compared the magnitude of diagnostic group differences separately among girls and boys for each of the subcortical structures despite the absence of a diagnostic group × sex × ROI interaction, F (3, 81) = 1.4, p = 0.242, d = 0.26. Among boys, although volume was generally reduced across all subcortical structures, there were no significant diagnostic group differences ( ps > 0.05), with medium effect sizes observed across all subcortical structures, ( ds ranging from 0.43 − 0.53), suggesting insufficient power to detect these effects.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on previous findings of ADHD-related sex differences in basal ganglia volumes (Qiu et al, 2009; Seymour et al, 2017), we compared the magnitude of diagnostic group differences separately among girls and boys for each of the subcortical structures despite the absence of a diagnostic group × sex × ROI interaction, F (3, 81) = 1.4, p = 0.242, d = 0.26. Among boys, although volume was generally reduced across all subcortical structures, there were no significant diagnostic group differences ( ps > 0.05), with medium effect sizes observed across all subcortical structures, ( ds ranging from 0.43 − 0.53), suggesting insufficient power to detect these effects.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a recently published study from our research group identified sex-differences in subcortical morphology (volume and shape) among school-age children (8–12 years) with and without ADHD (Seymour et al, 2017). In this older sample, boys with ADHD showed reduced volumes and localized compression in the globus pallidus and putamen, but not the caudate or thalamus, compared to TD boys, whereas no diagnostic group differences were observed in girls with ADHD compared to TD girls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations